PERSEPSI MAHASISWA TERHADAP PENGGUNAAN APLIKASI GOOGLE MEET DAN GOOGLE FORM DI MASA PANDEMI - Hevy Risqi Maharani; Mohamad Aminudin; Kisfatul Ummamah (Universitas Muria Kudus, 2022)
The purpose of this study is to describe students' perceptions of the use of Google Meet and Google Form.The research method used is descriptive using a survey method. Purposive sampling was used as a data collection technique. Data collection was carried out online using a questionnaire instrument and interviews with a sample of 34 students of the S1 Mathematics Education Study Program FKIP Unissula who used the Google Meet and Google Form applications when conducting lectures on algebra courses. The data collection technique is using Google Form, then data collection is carried out using the WhatsApp application using an unstructured interview instrument.The results showed that students' perceptions of the use of Google Meet and Google Form were classified as good criteria. This is because there are still obstacles in both applications. The constraint of the Google Meet application is the signal factor, an unstable signal will make users automatically leave Google Meet, while the problem with Google Form itself is the absence of math equation facilities. The hope is that there will be developments in the Google Meet and Google Form applications so that they can provide more comfort and convenience for their users.